Analisis Lingkungan Bisnis dan Strategi serta Pengaruhnya terhadap Kinerja Perusahaan Daerah Air Minum (PDAM) di Sulawesi - ., Mursalim (Universitas Brawijaya, Indonesia, 2012)
This study was developed with refer to the contingency theory in assessing the suitability ofgovernment intervention, strategy and performance of PDAM in Sulawesi. The purpose of this study are: (1)Explain the effect of government intervention on the efficiency and performance of PDAM, (2) Explain theinfluence of resources on the efficiency and performance of PDAM, (3) Explain the role of non-marketcapabilities in moderating the effect of government intervention on performance PDAM, (4) Explain theinfluence of efficiency on the performance of PDAM and (5) Explain the role of efficiency in mediating theeffect of government intervention, resources on the performance of PDAM in Sulawesi. Data was collectedusing a survey method at 60 PDAM in Sulawesi. In 60 PDAM is obtained only 54 stating willingness tobecome responden. Between 54 PDAM willing just, 50 questionnaires that may be analyzed by using PLS.The findings in this study are: (1) Financial assistance of local goverment is on time and the amount alongwith production capacity and optimal water distribution. (2) Financial assistance reinforced by communicationability of PDAM with local government side. (3) Availability of resources such as pipe lines, machineand pump according to the requirement.